6(3z-1)-4(z+3)=3(z+1)

Simple and best practice solution for 6(3z-1)-4(z+3)=3(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3z-1)-4(z+3)=3(z+1) equation:


Simplifying
6(3z + -1) + -4(z + 3) = 3(z + 1)

Reorder the terms:
6(-1 + 3z) + -4(z + 3) = 3(z + 1)
(-1 * 6 + 3z * 6) + -4(z + 3) = 3(z + 1)
(-6 + 18z) + -4(z + 3) = 3(z + 1)

Reorder the terms:
-6 + 18z + -4(3 + z) = 3(z + 1)
-6 + 18z + (3 * -4 + z * -4) = 3(z + 1)
-6 + 18z + (-12 + -4z) = 3(z + 1)

Reorder the terms:
-6 + -12 + 18z + -4z = 3(z + 1)

Combine like terms: -6 + -12 = -18
-18 + 18z + -4z = 3(z + 1)

Combine like terms: 18z + -4z = 14z
-18 + 14z = 3(z + 1)

Reorder the terms:
-18 + 14z = 3(1 + z)
-18 + 14z = (1 * 3 + z * 3)
-18 + 14z = (3 + 3z)

Solving
-18 + 14z = 3 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-18 + 14z + -3z = 3 + 3z + -3z

Combine like terms: 14z + -3z = 11z
-18 + 11z = 3 + 3z + -3z

Combine like terms: 3z + -3z = 0
-18 + 11z = 3 + 0
-18 + 11z = 3

Add '18' to each side of the equation.
-18 + 18 + 11z = 3 + 18

Combine like terms: -18 + 18 = 0
0 + 11z = 3 + 18
11z = 3 + 18

Combine like terms: 3 + 18 = 21
11z = 21

Divide each side by '11'.
z = 1.909090909

Simplifying
z = 1.909090909

See similar equations:

| 7+4w=-5 | | 2ln(7x)=-4 | | 3x-5=2x-3 | | .54-.07y=.2y | | 5y+4(y-7)=3(y+2)-5 | | 1.25*137= | | 5X+30=10(X*X) | | .75*137= | | 5s^2-8s=0 | | .25x-.125x=3-.0625x | | 4x+2(4y-3)=3 | | 12x-4=9x+72x | | -u^2-2u=16 | | -3(4y-5)(y+5)=0 | | 3w^2+4w+3=0 | | (7-k)(k-4)=0 | | 4x-13-5x=-12x+98x | | 0.7X+X=260927 | | u^2-u=-36 | | 3t+5(1-5t)= | | 3(3x-4)-8x=4-(6x+7) | | 6y=2y-12 | | 3x-(4+x)=26-20 | | 9z-3/8=9/16 | | 3x+1/2=5/4 | | -9=w/2-3 | | 5s^2+37s+42=0 | | b/3-12=-9 | | -3x=-14-3 | | 15years=hours | | 3(4x+4)=-4(x+5) | | 2(2x+3)=6(x+2) |

Equations solver categories